Stages of God's creation of man in the Koran stu - نبراس حسين مهاوش (College of Education for Women, 2019)
Thanks allah and peace be upon our prophet muhammed and upon his family and his followers...... The name is only called by the Almighty, One of the Names of the Creator Deity features and slavery. He is the idol who worshiped. The creator is derived from the creation of a sophisticated and significant from create Aharaz for crust, and tailor the gown and the end of launch on God's creation of the creature, and this release was a matter of metaphor One of the names of Allah, God is the creator himself is not a partner Creator of all things, is the one who created man from Nothingness began creating Adam peace be upon him and that he has passed the stages in the process of creation, namely: He created him from dust, and when you add water to him became mud and then turning mud to flesh elderly any clay black, and when dried mud became Salsala not be untouched by the fire, and then inflatable God of his soul Creating Adam, the first human beings. God Almighty has created man from clay Mitt not motionless in it and make his descendants out of the bottom of the crucifixion ofwater is weak, called a drop, then turned the sperm into a piece of blood frozen called leech then turned clot to the piece of meat small called embryo and then turned into a bone and then God meat again and then completed his creation and filmed and enter the spirit.